2022
DOI: 10.3390/en15145122
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Comparison of the Impact of Grass Silage Pulsed Electric Field and Microwave-Induced Disintegration on Biogas Production Efficiency

Abstract: Lignocellulosic biomass is included in the group of renewable energy sources. Its calorific value is high, owing to which it can be successfully used in the production of second-generation fuels, e.g., biogas. However, its complex structure makes it necessary to apply a pretreatment in order to increase the biogas output. This study presents the usability of a pulsed electric field in grass silage pretreatment in methane fermentation and compares it with microwave-induced disintegration. The experiment shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Methane productivity from pulsed electric field (PEF) pre-treated silage increased by 20.1% compared to the untreated control. The highest biogas output from PEF pre-treated samples was 535.57 L•kgVS -1 , while the highest biogas output from microwave pre-treatment substrates was 487.18 L•kgVS -1 [6]. During the 9 days of a fed-batch cycle, biohythane (biomethane and biohydrogen) production of 0.667 ± 0.054 L•Lreactor −1 (based on three fed-batch cycles) in alkali-pre-treated sludge fed MECs was obtained, compared to 0.451 ± 0.030 L•Lreactor −1 in raw sludge fed MEC and 0.383 ± 0.027 L•Lreactor −1 in raw sludge fed open circuit MEC [7].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Methane productivity from pulsed electric field (PEF) pre-treated silage increased by 20.1% compared to the untreated control. The highest biogas output from PEF pre-treated samples was 535.57 L•kgVS -1 , while the highest biogas output from microwave pre-treatment substrates was 487.18 L•kgVS -1 [6]. During the 9 days of a fed-batch cycle, biohythane (biomethane and biohydrogen) production of 0.667 ± 0.054 L•Lreactor −1 (based on three fed-batch cycles) in alkali-pre-treated sludge fed MECs was obtained, compared to 0.451 ± 0.030 L•Lreactor −1 in raw sludge fed MEC and 0.383 ± 0.027 L•Lreactor −1 in raw sludge fed open circuit MEC [7].…”
Section: Introductionmentioning
confidence: 95%
“…The use of electricity in promoting the potential of biogas has taken place in different directionsstarting with the use of a pulsed electric field in the pre-treatment of the input material [6] and ending with the placement of microbial electrolysis cells (MEC) in the bioreactor itself [7; 8]. Methane productivity from pulsed electric field (PEF) pre-treated silage increased by 20.1% compared to the untreated control.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was conducted by Deng et al [29], in which the COD content increased by approximately 29% following the application of the PEF treatment of sewage sludge. The effects of ultrasonic radiation treatment of lignocellulosic substrate on TOC and COD solubilisation were also investigated by Kisielewska et al [25]. The ultrasonic disintegration of Sida hermaphrodita increased the TOC and COD contents in the liquid fraction of the substrate by 24.7 and 21.9%, respectively.…”
Section: The Effect Of Up and Pef On Organic Matter Solubilisationmentioning
confidence: 99%
“…A voltage of 40 kV amplitude was applied to the electrodes. Based on the preliminary studies, the process parameters were selected [23][24][25]. The generated electrical pulses were characterised by a width of 50 µs and a frequency of 5 kHz.…”
Section: Pretreatmentmentioning
confidence: 99%
“…Studies carried out in France and Denmark showed that the total nitrogen amount in catch crops' biomass harvested on 1 hectare ranged from 10 to 171 kg N ha −1 for legumes, and from 9 to 89 kg N ha −1 for non-legumes, while the C:N ratio ranged widely, from 9 to 40, thus sometimes going beyond the range considered optimal for microorganisms' growth, which is estimated to be between 20 and 35 [113,114]. According to the study of Szwarc et al [99], the C:N ratio of grass silage was ca. 23.…”
Section: Features Of CCC Biomass Important Because Of Biochemical Con...mentioning
confidence: 99%